The influence of gender and social economic status on boarding school students' English language performance - Bidin, Samsiah; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
The purpose of this study was to describe the relationship between the students’ gender and Social Economic Status (SES) and the English Language performance. A total of 355 form four students from four boarding schools in the state of Kedah and Perlis were taken as the subjects for this study. The research tool used was in the form of a questionnaire. The measurement of student’s performance was based on their PMR English examination scores. The t-test and ANOVA were used to test the independent variables. The results obtained reported that gender, parents’ total monthly income, parents’ education level and the frequency of using English showed the existence of significant differences as related to the English Language performance. Other personal characteristics variables did not show any significant differences.